Pengembangan Lembar Kerja Siswa dengan Pendekatan Kerja Laboratorium untuk Meningkatkan Keterampilan Proses Fisika - Sulistiyono Sulistiyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
This research aims to produce Student Worksheet that is in suitable with the characteristics of laboratory work approach. This research also aims to cultivate the physics process skill of the students during the teaching of laboratory work.This is a Research and Development developed by Borg and Gall. The stages in this research are collecting information, making plan, developing initial product, conducting tryout, doing revision of the product. The initial tryout or limited tryout is done to grade 9 SMAN margabaru. The instrument is Lesson Plan, Student Worksheet validation sheet, physics process skill observation sheet, students response questionnaire. Data analysis is descriptive qualitative.The result shows that LKS developed based on expert validation test on the aspect of writing approach, the depth of physics concept, scoring aspects, student activity and physical appearance is in the criteria of very good. For LKS identity completeness, clarity of sentence and language is in the criteria of good. Meanwhile, the percentage of the physics process skill achievement as compiling the hypothesis, skill of identifying variables, skill of filling the tables, skill of making graphs, skill of investigation analysis and the skill of drawing conclusion, is 92 percent, 93 percent, 80 percent, 90 percent, 78 percent, dan 78 percent. Keywords: Student Worksheet (LKS), laboratoey work, physics process skill